A New Study on Tribological Performance of Cissus Quadrangularis Stem Fiber/Epoxy with Red Mud Filler Composite. Issue 9 (2nd September 2022) - Jenish, I.; Gandhi, V. C. Sathish; Raj, R. Edwin; Basavarajappa, S.; Indran, S.; Divya, D.; Kumaravelan, R.
ABSTRACT: Dry sliding friction and wear behavior, hardness, and thermogravimetric analysis (TGA) of Cissus quadrangularis stem fiber (CQSF)/epoxy resin composite, reinforced with red mud particulate filler were done. The hardness of the material increased by adding red mud filler. Thermogravimetric analysis (TGA) reveals that the maximum char yield obtained at 10 wt.% red mud particulate-filled with CQSF/epoxy composite. The optimization of dry sliding friction and wear behavior was done by response surface methodology (RSM) based on pin-on-disc wear test to determine the specific wear rate (SWR) and coefficient of friction (COF) of the materials. The experimental design was created with four input parameters at three different levels using full factorial central composite design (CCD). The minimum SWR was achieved at 5.93 wt.% red mud addition irrespective of other parameters, was obtained by RSM optimization technique. The scanning electron microscopy (SEM) images of the worn out surfaces substantiate the optimized results of wear properties.